The Influence of Motherâs Characteristics Toward Basic Complete Immunization Non-Compliance for Children Under-Two-Years - Harmasdiyani, Riska (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTMothers play a significant role in the children health. Immunization compliance measurement is used to assess basic complete immunization coverage as an indicator of successfull immunization program. The purpose of this study was to determine the influence of motherâs characteristics toward basic complete immunization non-compliance for children under- two-years. This study used observational analytic study and case control design. The number of sample in this study was 49 people for each group of case and control with cluster random sampling technique. This study used a logistic regression test and Odds Ratio to determine the significant variable. The results showed that motherâs education and knowledge risk for basic complete immunization non-compliance. Low educated mothers have 9,281 higher risk towad basic complete immunization non-compliance than high educated mothers. Mothers with less knowledge have 20,9 higher risk toward basic complete immunization non-compliance than mothers with good knowledge. It is conclude that motherâs characteristics that affect to basic complete immunization non-compliance are motherâs education and knowledge. Increasing motherâs attendance to Posyandu and health workersâ role through Information, Education and Communication (EIC) will improve motherâs knowledge. It will increase motherâs motivation giving immunization for children to decrease basic complete immunization non-compliance.Keywords: education, knowledge, non-compliance, basic complete immunization, under-two-years